Effect of ar-Rahnu relationship value on long-term relationship between customer and institutions - Rafidah Mohd Azli,; Mohd Rizal Palil,; Shifa Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ar-Rahnu is a concept of Islamic debt with pledged item. In Malaysia, Ar-Rahnu concept is applied by Islamic pawn broking industry. Thus, the practitioners called Islamic Pawn broking product as “Ar-Rahnu.” There are no studies that conceptualize relationship value of Ar-Rahnu and its dimensions as the decisive factor in Ar-Rahnu development in Malaysia. Study of long-term relationship between customer and institutions can be an indicator of Ar-Rahnu development. The long-term relationship study proves and verifies the transparency of business. However, the study about the decisive factors of long-term relationship in Ar-Rahnu industry is lacked. The aim of this paper is to prove the effect of Ar-Rahnu relationship value and its dimensions towards the long-term relationship between customer and institutions. This research is conducted among Ar-Rahnu customers within seven Ar-Rahnu institutions which are situated in Central Zone of Malaysia. Two hundred and six respondents were selected to answer a set of adapted questionnaires. The conceptual model of this paper has been validated by the confirmatory factor analysis (CFA). The analysis of Structural Equation Modeling (SEM) shows that all the dimensions of Ar-Rahnu ‘benefits’ produce a significant effect on long-term relationship but the ‘sacrifices’ give insignificant effect. The finding can improve the shariah justification on Islamic pawn broking. The value of this study lies in its effort to propose to practitioners the enhancement of marketing system regarding the most preferences and matter of concern by customers about Ar-Rahnu product.